Key role of learning by observing and pitching in (LOPI) in the resilience of Yucatec Maya food systems: foundations for culturally sensitive extension programs - Rosado-May, Francisco J.; Caamal Itzá, Bernardo; Cuevas-Albarrán, Valeria B.; Mukul, Loida Briceño (Frontiers in Sustainable Food Systems, 2025)
The biodiversity in traditional Yucatec Maya food systems is well known and documented. However, over time, more and more Indigenous farmers are incorporating inputs related to the Green Revolution, harming biodiversity, beekeeping, and changing the design and management of the food systems. Thus, traditional resilience and biodiversity are threatened. To understand whether the resilience and biodiversity of Yucatec Maya food systems are related to their cultural ways of learning, information was gathered using the Yucatec Maya method called tsikbal in four Maya communities. In each community, two collaborating farmers were selected: one had been farming for at least 20 years using only traditional methods, and the other had been farming, incorporating elements of the Green Revolution, for at least 10 years. The information was organized based on the seven features of a paradigm called Learning by Observing and Pitching In, which emerged from several studies on how children in Indigenous communities, mostly Maya, learn. The results suggest that traditional farmers keep high biodiversity in their food system because their decisions and actions are based on the same features learned in their childhood. Based on these results, it is possible to suggest that the resilience and biodiversity of Yucatec Maya food systems are explained by their cultural ways of learning and creating knowledge developed over time. When Yucatec Maya farmers introduce practices from other ways of knowing and adapt their local learning methods, the resilience and biodiversity of their food systems are negatively affected. These findings can be applied to extension programs to help transform broken Indigenous food systems.